2009
DOI: 10.1128/aem.02600-08
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Cellulose Degradation and Electricity Production by Enterobacter cloacae in a Microbial Fuel Cell

Abstract: Electricity can be directly generated by bacteria in microbial fuel cells (MFCs) from many different biodegradable substrates. When cellulose is used as the substrate, electricity generation requires a microbial community with both cellulolytic and exoelectrogenic activities. Cellulose degradation with electricity production by a pure culture has not been previously demonstrated without addition of an exogenous mediator. Using a specially designed U-tube MFC, we enriched a consortium of exoelectrogenic bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(100 citation statements)
references
References 42 publications
2
94
1
3
Order By: Relevance
“…These genera have been described in active sludges from wastewater treatment (Khan, 2002;Sohn et al, 2004;Zhua et al, 2008;Sarma et al, 2010) and polycyclic aromatic hydrocarbon-contaminated soils (Achuthan et al, 2006). E. cloacae has been recently reported as able to produce electricity in an MFC (Rezaei et al, 2009). Therefore, the bacteria identified in the present study are congruent with reports regarding similar samples.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These genera have been described in active sludges from wastewater treatment (Khan, 2002;Sohn et al, 2004;Zhua et al, 2008;Sarma et al, 2010) and polycyclic aromatic hydrocarbon-contaminated soils (Achuthan et al, 2006). E. cloacae has been recently reported as able to produce electricity in an MFC (Rezaei et al, 2009). Therefore, the bacteria identified in the present study are congruent with reports regarding similar samples.…”
Section: Discussionsupporting
confidence: 82%
“…The electrons are transferred to the cathode compartment through an external electric circuit; meanwhile, the protons are transferred to the cathode compartment through the membrane. MFCs provide dual benefits of wastewater treatment and the production of inexpensive and environmentally friendly energy; this technology has been increasing in importance worldwide over the last decade because of its sustainability (Logan et al, 2006;Kumlanghan et al, 2007;Mohan et al, 2009;Rezaei et al, 2009;Ryu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of BESs when using two compartments is that they not solely convert compounds but also separate oxidation and reduction products, which makes it possible to extract useful products out of wastes. Nowadays, BES with bioanodes uses electron donors derived from wastes (e.g., wastewaters; Logan 2005), sediments (Reimers et al 2001), processed energy crops (as cellulose; Niessen et al 2005;Ren et al 2007;Rezaei et al 2009), photosynthetic microorganisms (Strik et al 2008b;Chiao et al 2006;Fu et al 2009), or in situ photosynthesized plant rhizodeposits (Strik et al 2008a;De Schamphelaire et al 2008). BESs, like MFCs treating wastewater, combine energy harvesting with necessary wastewater cleaning.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows the performance of the MFCs using cellulose biomass as substrates. It was found that both cellulolytic and exoelectrogenic microorganisms would be required for electricity generation in BES, because no single strain has yet been capable of producing electricity directly from cellulose [39,40]. An early study reported indirect electricity generation from cellulose in an MFC, through in situ oxidation of hydrogen that was produced from the anaerobic degradation of cellulose by cellulolytic bacteria (Clostridium cellulolyticum and Clostridium thermocellum) [41].…”
Section: Plant Wastementioning
confidence: 99%